RUDIST FACIES DISTRIBUTION IN THE LATE CRETACEOUS OF CILENTO AND WESTERN BASILICATA (SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Rudist bivalve assemblages and biofacies spanning from the Cenomanian to the Maastrichtian age interval have been detected in ten selected fossiliferous localities of Cilento and western Basilicata (southern Apennines, southern Italy). Their distribution shows a lateral transition from inner platform with mono-oligospecific radiolitid assemblages of the late Turonian - Coniacian, to more open depositional settings with well diversified fauna of the Santonian-Maastrichtian passing from south-western to eastern Cilento. In western Basilicata, prevailing grain-supported sediments and well diversified caprinid assemblages are indicative of open shelf and margin depositional settings of early - middle Cenomanian age. Furthermore, stratigraphic data point out (1) the lack of the Santonian - Maastrichtian deposits toward south is referred to incipient emersion of this sector of the Apennine Carbonate Platform (ACP), (2) the overall biofacies distribution also has to be related to the setting of the ACP as regards the paleooceanic circulation during the Late Cretaceous and (3) the occurrence of “out of context” radiolitid beds at Raparo Mt., up to now referred as a klippe, could be regarded as a still open point to discussion concerning its paleogeographic attribution.
Keywords: Rudists; Bivalves; Biofacies; Biostratigraphy; Carbonate platform; Tethys; Late Cretaceous; Paleogeography; Southern Apennines